PEMBELAJARAN INKUIRI SEBAGAI UPAYA PENINGKATAN BERPIKIR KRITIS DAN KOMUNIKASI MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA - Erika Nora Simamora (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2009)
The study was conducted to improve the ability of critical thinking and mathematical communication students of SMP Negeri 14 Medan. This was an experimental study where the population is all students in grade IX SMP Negeri 14 Medan, which consisted of five classes. Samples were selected at random simple two classes so that the selected class IX (D) to control the class and class IX (E) be a class experiment where each class consists of 40 students. The instruments used in this study namely, tests of critical thinking skills and communication ability test shaped mathematical description of each test consists of 4 questions. The instrument has been tested and found valid and the reliability coefficient of 0.935 and 0.95 respectively for the ability of critical thinking and mathematical communication skills. The test is given twice before (pretest) and after (posttest) of learning. Conclusion of the study: (1) increase students 'critical thinking skills inquiry learning junior who received 0.3974 (39.74%) better than students who received conventional learning 0.274 (27.40%), (2) improving students' mathematical communication skills junior who received inquiry learning 0.3317 (33.17%) better than students who received conventional learning 0.257 (25.70%), (3) the pattern of responses of the students who followed the inquiry learning better than students who received conventional teaching based on value scores obtained by each class.